Hybrid trans‐apical atrioventricular valve‐in‐valve implantation in Fontan circulation. Issue 5 (8th January 2020) - Butera, Gianfranco; Lucchese, Gianluca; Austin, Conal; Frigiola, Alessandra
Abstract: Trans‐apical approach has been proved successful in failing surgical bio‐prosthesis in both mitral and aortic position in adult patients. Recently, valve‐in‐valve treatments have been applied even in patients with complex congenital heart disease. Here, we report the case of a 32 years old lady with left atrial isomerism, complete AV septal defect, interrupted inferior vena cava with azygos continuation who underwent Kawashima procedure with atrial Fontan. Severe systemic atrioventricular valve regurgitation necessitated a 33 mm Perimount valve implantation and conversion to lateral tunnel Fontan. After only 4 years there was severe valve stenosis and the patient underwent successful trans‐apical transcatheter implantation of a 29 mm Sapien valve.